2022
DOI: 10.3390/diagnostics12010178
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trabecular Bone Score-Adjusted Fracture Risk Assessment Tool with Coronary Artery Calcification in Women

Abstract: The trabecular bone score (TBS) was found to be significantly associated with moderate coronary artery calcification (CAC). The aim of this study was to further explore the association between TBS-adjusted Fracture Risk Assessment Tool (FRAX) and CAC score in women. The electronic medical record database of a regional teaching hospital in southern Taiwan yielded women who received both coronary computed tomography and bone mineral density (BMD) measurement during their general health examination. Health histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“… 35 However, another study reported that a significant association of CACs with an increase of osteoporotic fracture and hip fracture risk. 36 These studies implied that the included subjects and BMD sites may be critical when analyzing the association of these two. Our study firstly found a negative association between CACs and BMD in T2DM patients with visceral obesity.…”
Section: Discussionmentioning
confidence: 99%
“… 35 However, another study reported that a significant association of CACs with an increase of osteoporotic fracture and hip fracture risk. 36 These studies implied that the included subjects and BMD sites may be critical when analyzing the association of these two. Our study firstly found a negative association between CACs and BMD in T2DM patients with visceral obesity.…”
Section: Discussionmentioning
confidence: 99%